2013
DOI: 10.5935/0101-2800.20130022
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis in the elderly patient: a challenge of the XXI century - narrative review

Abstract: With the increase in life expectancy, the improvement of therapeutic arsenal, knowledge and control of chronic degenerative diseases, the world population has reached older age groups. As advanced age is a risk factor for chronic kidney disease (CKD), along with the bonus of increased survival, today we are experiencing the greatest burden of progressive incidence of elderly patients on renal replacement therapy (RRT). Dialysis in elderly patients, which for three decades was considered out of question, today … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 79 publications
(91 reference statements)
1
13
0
Order By: Relevance
“…This could be in conflict with the current clinical practice guidelines. In fact, strict application of these recommendations may be inappropriate for certain patients (3,(10)(11)(12).…”
Section: Discusionmentioning
confidence: 99%
“…This could be in conflict with the current clinical practice guidelines. In fact, strict application of these recommendations may be inappropriate for certain patients (3,(10)(11)(12).…”
Section: Discusionmentioning
confidence: 99%
“…According to demographic data, it is also happening in other nations because the population ageing is a global phenomenon. Regarding the number of elderly people in each country of the world, it is believed that Brazil will occupy the sixth place by 2025 [1].…”
Section: Introductionmentioning
confidence: 99%
“…The 2013 Australian and New Zealand Dialysis and Transplantation Registry further revealed that there were 2484 people aged 75 years and above receiving haemodialysis, being 27% of all haemodialysis patients, and this number includes 447 people aged over 85 years, a rise of 7% from 2011 . This trend has been attributed to an increase in the life expectancy, improvement of the therapeutic arsenal, and knowledge and control of comorbid diseases . As a result, the number of elderly patients requiring replacement therapy is growing.…”
mentioning
confidence: 99%
“…2 This trend has been attributed to an increase in the life expectancy, improvement of the therapeutic arsenal, and knowledge and control of comorbid diseases. 3 As a result, the number of elderly patients requiring replacement therapy is growing. Several studies have also noted this drastic increase of the elderly population receiving dialysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation